Berberine as Source of Antiproliferative Hybrid Compounds: In Vitro Antiproliferative Activity and Quantitative Structure-activity Relationship - Leyva-Peralta, Mario A.; Robles-Zepeda, Ramón E.; Razo-Hernández, Rodrigo S.; Berber, Laura P.Á.; Lara, Karen O.; Ruiz-Bustos, Eduardo; Gálvez-Ruíz, Juan C. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Despite advances for cancer treatment, it still remains a major worldwide public health problem. Compounds derived from natural sources are important alternatives to combat this mortal disease. Berberine is an isoquinoline alkaloid with a wide variety of pharmacological properties, including antiproliferative activity. Previously, we have found that fatty acids also show antiproliferative activity against cancer cell lines. Objective: To combine berberine and fatty acids, or carboxylic acids, in order to improve their antiproliferative properties. Methods: We synthetized six new hybrid derivatives through a simple methylenedioxy group-cleavage method followed by the reaction with fatty acids, or carboxylic acids. The structure of the compounds was elucidated by IR, NMR and HRMS. The in vitro antiproliferative activity against four human cancer cell lines (HeLa, A-549, PC-3 and LS-180) and one normal cell line (ARPE-19), was evaluated by the MTT method. Chemical structures were drawn using SPARTAN '08 software and the conformational analysis was carried out with a molecular mechanic level of theory and the SYBIL force field. All molecular structures were subjected to geometrical optimization at the semi-empirical method PM3. Molecular descriptors were calculated using DRAGON 5.4 and SPARTAN ´08 programs. Results: The geranic acid and berberine hybrid compound (6) improved the antiproliferative activity shown by natural berberine, even more than the 16- to 18-carbon atoms fatty acids. Compound 6 showed IC50 values of 2.40 ± 0.60, 1.5 ± 0.24, 5.85 ± 1.07 and 5.44 ± 0.24 μM, against HeLa, A-549, PC-3 and LS-180 human cancer cell lines, respectively. Using this information, we performed a quantitative structure-activity relationship (QSAR) of the hybrid molecules and found that the molecular descriptors associated with the antiproliferative activity are: hydrophobic constant associated with substituents (π(A) = 6.5), molecular volume descriptor (CPKvolume≈ 700 Å3), EHOMO, number of rotatable bonds (RBN) and number of 6-membered rings (nR06). Conclusion: The methylendioxy and methoxyl groups in berberine are important for the antiproliferative activity shown by its derivatives. Better results in antiproliferative activity were obtained in compound 6 with the prenyl moiety. The QSAR indicates that the molecular descriptors which associated positively with the antiproliferative activity are: hydrophobic constant associated with substituents (π(A) = 6.5), molecular volume descriptor (CPKvolume≈ 700 Å3) and EHOMO. This research gave the basis for the design and preparation of new, easily afforded molecules derived from berberine and carboxylic acids, with improved antiproliferative activity.
Keywords: alkaloids